Structure and genomic organization of I elements involved in I-R hybrid dysgenesis in Drosophila melanogaster. - Crozatier, M (1988)
I-R hybrid dysgenesis in D. melanogaster is controlled by transposable elements known as I factors which terminate at their 3' ends by an A-rich sequence. Inducer strains contain active I factors. Both reactive and inducer stocks possess defective I elements. We have cloned various I elements from both categories of strains. The I elements having recently transposed in inducer strains have a structure closely related to that of active I factors. However we have isolated one such I element that is truncated at its 5' end. The I elements common to reactive and inducer strains are affected by various rearrangements and many point mutations. They do not appear to be simple derivatives of complete I factors.